THE FOREIGN LANGUAGE STUDENT AS AN ETHNOGRAPHER: LANGUAGE GAMES AND ETHNOGRAPHIC TECHNIQUES FOR ENHANCING THE DEVELOPMENT OF INTERCULTURAL COMPETENCE THROUGH STUDYING FOREIGN LANGUAGE CULTURE - Owczarek , Dorota (Neofilolog, 2020)
The present paper aims at finding ways to solve the problem of how to teach culture, showing the connections between culture and language, while at the same time striving to develop intercultural competence. In the author’s opinion, the ethnography of speaking is the answer. Starting with an overview of what ethnography offers to intercultural communicative competence, this paper supports the idea of implementing an approach close to the ethnography of speaking and shows how linguistic ethnography might be implemented into the study of culture in order to show the relationships between language use, cultural behavior and values. This approach rests upon the belief that the implicit knowledge applied in use of a language needs deeper analysis in order to enhance students’ symbolic competence, which in turn enhances their intercultural competence. Examples used in the analysis to justify this claim derive from material used during a course in General English, or courses of British and American Studies. The concept of language-games as proposed by Wittgenstein, who pays attention to the context of language use at the micro level, is applied. The suggestion is to position this analysis in the field of the ethnography of speaking, or linguistic ethnography, and extend the role of a student to one of a linguistic ethnographer. Ethnographic techniques implemented in the analysis of language use and its context might contribute to the development of symbolic competence as complementary to intercultural communicative competence.